Infant With In Utero Ketamine Exposure: Quantitative Measurement of Residual Dosage in Hair - Pen-Hua Su; Yan-Zin Chang; Jia-Yuh Chen (Pediatrics and Neonatology)
The drug ketamine is frequently abused for recreational use in Asia, but few studies in humans have focused on the effects of ketamine exposure during pregnancy on the health of neonates. Here, we report a neonate whose mother was suspected of ketamine abuse during pregnancy. The case was confirmed by testing hair samples of the neonate. Methods: Hair samples of the neonate were taken on the first day of referral. Levels of common drugs of abuse in Asia were measured in the hair sample by gas chromatography-mass spectrometry using our previously reported method with modifications. This method was developed and validated to simultaneously quantify levels of amphetamine, ketamine and opiate in human hair. Results: The neonate was a female baby, born full term, with a low birth weight of 2250 g. Very high levels of ketamine were detected in the neonate's hair, even though the mother stated that she had stopped abusing ketamine during the early stage of pregnancy. The neonate suffered from general hypotonia; moderate cerebral dysfunction was found by electroencephalography. Fortunately, her hypotonia improved gradually within 21 days. Conclusion: This is the first report of ketamine exposure during late pregnancy detected by hair testing. We noted several clinical features in this case, including the infant being small for gestational age, intrauterine growth retardation, remarkable hypo-tonia, and poor reflex responses. Although the mother denied the use of ketamine during the late stage of her pregnancy, significant amount of ketamine and norketamine was still found in hair samples (only 2 cm long and 25 mg) from the infant.